Pengaruh Kualitas Website, Persepsi Risiko Dan Kepercayaan Tehadap Keputusan Pembelian Pada Pelanggan Shopee (Studi Pada Mahasiswa FEB UNISMA Kota Malang) - Zulkhaeri, Zulkhaeri; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This quantitative study investigates the impact of website quality, risk perception, and trust on the purchasing decisions of Shopee customers among students at FEB UNISMA Malang City. Utilizing the Malhotra formula, a sample size of 72 was determined. SPSS software was employed to analyze the data through validity, reliability, and normality tests, multiple linear regression analysis, multicollinearity, heteroscedasticity, F-tests, and t-tests. The findings indicate that website quality (X1) and risk perception (X2) significantly and partially influence purchasing decisions (Y). Conversely, trust (X3) does not exhibit a significant partial effect on purchasing decisions (Y). Keywords: Website Quality, Risk Perception, Trust, Purchasing Decisions.